Improvement of photovoltaic systems with tracking of the maximum power point in low-irradiation atmospheric conditions - Djanssou, Dieudonné Marcel; Abdouramani, Dadjé; Kwefeu Mbakop, Fabrice; Djongyang, Noël (Jurnal Elektronika dan Telekomunikasi, 2023)
This paper discusses the efficient use of photovoltaic energy in areas with low solar irradiation. To extract the maximum power at low irradiation, we used a maximum power point tracking (MPPT) algorithm based on the combination of fuzzy logic (FL) and the sliding mode (SM) associated with a Proportionnel-Intégral (PI) regulator. The system parameters are calculated using the particle swarm optimization (PSO) technique, which thus ensures the stability of the controller. The performance of the proposed technique is compared with the conventional perturb and observe (P&O) technique in terms of tracking time and tracking efficiency at low irradiation. The simulation results prove that the technique has high tracking efficiency and less convergence time under low irradiation, with fewer power oscillations, low ripple and no overshoot.